Network and design concepts for accommodating large trucks at roundabouts - Godavarthy, Ranjit Prasad (Kansas State University, 2012)
It has been well documented that roundabouts can offer several safety and operational benefits over signalized and stop controlled intersection alternatives. However the growing use of roundabouts and their benefits could be greatly diminished because they may not be well designed for large trucks, or to accommodate oversize/overweight (OSOW) vehicles which may be essential to a state’s industry and economy. This dissertation addresses concepts to better design roundabouts for use by owners/operators of typical large trucks, and that will also accommodate OSOW vehicles where appropriate. Roundabout safety generally decreases with increased roundabout size, wider lanes and larger radii, the geometric parameters that benefit large trucks and OSOW, thus a better balance is needed. This study accomplishes this balance by initially reviewing and incorporating those portions of the study “Accommodating Oversize Overweight Vehicles at Roundabouts” that were researched, completed and written by the author of this dissertation, and which compiled current practice, research and concerns by various U.S. states and concerns of the trucking industry, by conducting four different surveys. Then to meet these concerns expressed by survey respondents, a great number of possible accommodation, strategies and design templates were developed by using existing design software. An evaluation method was also developed. Two additional, needed studies, not previously reported in any published literature, addressed : 1. a vertical, ground clearance analysis, and 2. a study of the use of roundabouts in urban freight networks to incorporate their inherent benefits ,such as, reducing congestion, delay and pollution. The first analysis described above was conducted by using software with 3D analysis capabilities to check and recommend critical vertical grades and maximum dimensions for a range of large truck types and OSOW vehicle configurations. Guidelines were developed to avoid problems of low, ground clearance vehicles scraping roundabout surfaces (“hanging up”). The second study used existing software that relates intersection types to intersection traffic flow efficiency and related pollution, on a number of routing scenarios to test the hypothesis that integration of roundabouts in these freight networks improves traffic flow, and decreases delay, congestion and pollution. The results were mixed but the procedure is sound and should be beneficial for future use by researchers and decision makers.
Keywords: Trucks; Oversize/overweight vehicles; Freight networks; Roundabouts; Transportation (0709)